2022
DOI: 10.1002/emp2.12693
|View full text |Cite
|
Sign up to set email alerts
|

Multisite study of Aggressive Behavior Risk Assessment Tool in emergency departments

Abstract: By JACEP Open policy, all authors are required to disclose any and all commercial, financial, and other relationships in any way related to the subject of this article as per ICMJE conflict of interest guidelines (see www.icmje.org). The authors have stated that no such relationships exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 18 publications
1
20
0
1
Order By: Relevance
“…Several tools have been published more recently that are focused on screening for violence in the ED setting. [22][23][24]27,28 However, HCWs in the ED should consider using systematic violence screening tools that encompass their patient population and the type of violent events and situational triggers that occur in their ED setting. Viewing patient-to-staff violence through the SEM framework 29 can contextualize the patient population, types of violent events, antecedents and precedents of violent events, violence, and clinical history typically identified in each unique ED setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several tools have been published more recently that are focused on screening for violence in the ED setting. [22][23][24]27,28 However, HCWs in the ED should consider using systematic violence screening tools that encompass their patient population and the type of violent events and situational triggers that occur in their ED setting. Viewing patient-to-staff violence through the SEM framework 29 can contextualize the patient population, types of violent events, antecedents and precedents of violent events, violence, and clinical history typically identified in each unique ED setting.…”
Section: Discussionmentioning
confidence: 99%
“…Several tools have been published more recently that are focused on screening for violence in the ED setting 22–24,27,28. However, HCWs in the ED should consider using systematic violence screening tools that encompass their patient population and the type of violent events and situational triggers that occur in their ED setting.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating the VEST into EHR could allow the simple and easy collection of WPV regularly as a part of routine nursing assessments. Our previous studies of patient violence in medical-surgical units and emergency departments indicated that the violence occurs in 1% to 3% of the patients 20,21 . For nonviolent patients, the VEST can be completed quickly by responding “no” to the 1st question of whether any violent event has occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Using a validated risk-screening tool may assist staff in identifying patients at high risk for violence and allow the implementation of focused, preemptive violence prevention measures. In our previous studies, Aggressive Behavior Risk Assessment Tool (ABRAT) was effective in identifying potentially violent patients with satisfactory sensitivities and specificities in acute care medical-surgical units and emergency departments 20,21 . Focusing preventive interventions on a small fraction of the patients at high risk of violence could allow better resource utilization than an indiscriminate, universal precaution recommended by the Occupational Safety and Health Administration 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation